2012
DOI: 10.1242/jcs.112029
|View full text |Cite
|
Sign up to set email alerts
|

PINCH-1 promotes Bcl-2-dependent survival signalling and inhibits JNK-mediated apoptosis in the primitive endoderm.

Abstract: SummaryThe focal adhesion (FA) protein PINCH-1 is required for the survival of primitive endoderm (PrE) cells. How PINCH-1 regulates this fundamental process is not known. Here, we use embryoid bodies (EBs) and isolated EB-derived PrE cells to investigate the mechanisms by which PINCH-1 promotes PrE survival. We report that loss of PINCH-1 in PrE cells leads to a sustained activity of JNK and the proapoptotic factor Bax. Mechanistically, the sustained JNK activation was due to diminished levels of the JNK inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 38 publications
(74 reference statements)
2
26
0
Order By: Relevance
“…Moreover, activation of the phosphorylation of the Src family kinase and ERK1/2 is promoted by PINCH-1 (18). In the PrE, PINCH-1 is a pro-survival factor, which prevents apoptosis of PrE cells by modulating two independent signalling pathways; PINCH-1 inhibits JNK-mediated apoptosis by stabilizing the PINCH-1 binding protein RSU-1 and promotes Bcl-2-dependent pro-survival signalling downstream of integrins (13). In the present study, a correlation was identified between the activation of ERK signaling and the suppression of JNK signaling with the expression of PINCH in IAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, activation of the phosphorylation of the Src family kinase and ERK1/2 is promoted by PINCH-1 (18). In the PrE, PINCH-1 is a pro-survival factor, which prevents apoptosis of PrE cells by modulating two independent signalling pathways; PINCH-1 inhibits JNK-mediated apoptosis by stabilizing the PINCH-1 binding protein RSU-1 and promotes Bcl-2-dependent pro-survival signalling downstream of integrins (13). In the present study, a correlation was identified between the activation of ERK signaling and the suppression of JNK signaling with the expression of PINCH in IAs.…”
Section: Discussionmentioning
confidence: 99%
“…Functional studies have revealed that PINCH loss-of-function leads to embryonic lethality and displays an abnormal epiblast polarity, impaired cavitation, detachment of primitive endoderm (PrE) and severe apoptosis of the PrE (11,12). PINCH-1 promotes B-cell lymphoma (Bcl)-2-dependent survival signalling and inhibits c-Jun N-terminal kinase (JNK)-mediated apoptosis in the PrE (13). Although the function of PINCH remains unknown, increasing numbers and accumulating evidence indicates that PINCH has been correlated with cancer development, invasion and metastasis in malignant cells, including breast cancer (14), pseudomyxoma peritonei (15), gastric adenocarcinoma (16) and rectal cancer (17).…”
Section: Introductionmentioning
confidence: 99%
“…The Ras suppressor protein 1 (Rsu1) is a leucine rich repeat protein that has a role in the IPP complex activity via binding to the LIM 5 domain of the adaptor protein PINCH1 (Kadrmas et al 2004; Dougherty et al 2005). Rsu1 co-localizes with PINCH1 at sites of focal adhesions in mammalian cells and muscle cell attachment in Drosophila (Kadrmas et al 2004; Dougherty et al 2005; Dougherty et al 2008; Montanez et al 2012). The inhibition of PINCH-ILK or PINCH-Rsu1 interaction results in decreased cell spreading and reduced motility of mammalian cells (Tu et al 1999; Zhang et al 2002a, b; Dougherty et al 2005) such that Rsu1 and PINCH1 are independently required for migration in the mammary epithelial cell line MCF10A (Simpson et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the level of Rsu1 correlate with altered JNK activity (Masuelli and Cutler 1996; Kadrmas et al 2004; Dougherty et al 2005). Transient expression of Rsu1 in Cos1 cells inhibited growth factor-induced Jun kinase activity, and the ectopic expression of Rsu1 reduced JNK phosphorylation and apoptosis in PINCH1-deleted mouse primitive endoderm cells (Montanez et al 2012). Furthermore, Rsu1 is required for the viability of Drosophila embryos with disrupted PINCH-ILK binding (Elias et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that PINCH was involved in cell adhesion, migration, and apoptosis [13, 14]. PINCH protein can interact directly with integrin-linked kinase (ILK) and Nck-2 protein and is associated with integrin signaling and growth factor signaling pathway [1518].…”
Section: Introductionmentioning
confidence: 99%